The Effectiveness of Solution-Focused Brief Counseling in Improving Internal Locus of Control among Students with Academic Procrastination - Musyarofah, Nury Awalia; Isti’adah, Feida Noor Laila; Sugara , Gian Sugiana (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to determine the effect of solution-oriented brief counseling on increasing internal locus of control in students who experience academic procrastination. The research subjects are students with low internal locus of control criteria and high academic procrastination, which will be used as experimental objects. The method used is an experiment with the Single Subject Research (SSR) method with an A-B-A design. The instrument used is a questionnaire on locus of control and academic procrastination made through Google Forms. Visual analysis compared observation results in three conditions: Baseline A1 (before intervention). Baseline B (Intervention), Baseline A2 (After Intervention). All three results showed an increase in the frequency of internal locus of control in students who experienced academic procrastination from low to high. Interventions using solution-focused brief counseling proved effective. Schools can use this counseling as a preventive effort to improve internal locus of control in students who experience academic procrastination. The contribution of the results of this study as a foundation in developing or modifying brief counseling models to focus on aspects of internal locus of control as a key in increasing student responsibility for student academic tasks.